MEDICAL ERROR AND OUR ATTITUDE TOWARDS IT. COMMENTS ON THE ARTICLE «STRUCTURE OF MEDICAL ERRORS AND SURVIVAL OF PATIENTS IN THE INTENSIVE CARE DEPARTMENTS» - A. U. Lekmanov (Вестник анестезиологии и реаниматологии)
.